The family system as a socio-ecological determinant of bullying among urban high school adolescents in Gweru, Zimbabwe: implications for intervention - Ncube, Neddie (Canadian Center of Science and Education, 2021)
The study sought to identify family-related socio-ecological determinants of bullying among Gweru urban High school adolescents. A survey design, premised on the qualitative and quantitative paradigms, was used. From the 13 High schools, 2 day-and 2 day-boarding schools were selected using stratified random sampling. Each school had 1 purposively sampled class giving a total of 4 classes comprised of 149 students, from whom 16 bullies were identified. Four class teachers, 1 from each school were consecutively sampled. Bullies responded to questionnaires whereas class teachers had structured interviews. Data was respectively subjected to Spearman’s rho correlational computations between determinants and to thematic analysis. Major findings were that the socio-ecological determinants exerted a great influence on bullying, and that they had complex interactions between them. The overall conclusion was that the most influential determinants comprised of malfunctioning family set-ups. Recommendations included that anti-bullying intervention designers could take into cognizance that the identified determinants needed to be addressed, not in their individual capacities, as a change in one is likely to influence a change in others.